Pengaruh Pemberian Informasi Masa Subur dan “Flo Health” Terhadap Tingkat Pengetahuan Calon Pengantin di Semarang - Maulidya Al-Frida; Agnes Isti Harjanti; Mudy Oktiningrum (Pusat Riset dan Inovasi Nasional, 2025)
The Semarang City Health Office reported that in 2022, there were 15 maternal deaths out of 22,030 live births, or 67.5 per 100,000 KH. Furthermore, 19% of prospective brides at the Gunungpati Semarang Health Center with risky health issues are required to delay pregnancy by monitoring their fertile period. However, 91% of these prospective brides expressed confusion and were unaware of their fertile period and the Flo Health app. This study aims to analyze the effect of providing information on the fertile period and using Flo Health on increasing the knowledge of prospective brides. The research design used was a quasi-experimental design with a One Group Pre-Test and Post-Test approach. The population in this study consisted of prospective brides at the Gunungpati Semarang Health Center. The sampling technique used was accidental sampling, with 63 respondents. The statistical test employed was the normality test using Kolmogorov-Smirnov, followed by the Wilcoxon test, which resulted in a p-value of 0.000. This indicates that Ha is accepted, meaning there is an effect of providing information about the fertile period and using Flo Health on the knowledge level of prospective brides at the Gunungpati Semarang Health Center.